2010
DOI: 10.1016/j.cryobiol.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of centrifugation and sugar supplementation on the semen cryopreservation of captive collared peccaries (Tayassu tajacu)

Abstract: The present study is aimed at evaluating the effect of centrifugation for seminal plasma removal and the supplementation of fructose or glucose to the Tris-based extender on the kinematic patterns of the motility parameters of frozen-thawed semen obtained from captive collared peccaries (Tayassu tajacu). Semen samples (n = 14) were collected from 10 sexually mature male collared peccaries by electroejaculation. These samples were further evaluated for parameters such as motility, vigor, sperm viability, membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
2
30
1
Order By: Relevance
“…Date contains a variety of nutrients such as carbohydrate, protein, antioxidant, and vitamin C that might act as spermatozoa protectants. Sugar contents like sucrose (Rizal et al, 2007), glucose, fructose, and others (Castelo et al, 2010) in extender serve as extracellular cryoprotectants that might protect plasma membrane from damage during cryopreservation (Mukminat et al, 2014;Rizal et al, 2007). Karp (2010) stated that carbohydrate in a cellular environment can be associated with lipid or protein of plasma membrane of cells.…”
Section: Fresh Semen Qualitymentioning
confidence: 99%
“…Date contains a variety of nutrients such as carbohydrate, protein, antioxidant, and vitamin C that might act as spermatozoa protectants. Sugar contents like sucrose (Rizal et al, 2007), glucose, fructose, and others (Castelo et al, 2010) in extender serve as extracellular cryoprotectants that might protect plasma membrane from damage during cryopreservation (Mukminat et al, 2014;Rizal et al, 2007). Karp (2010) stated that carbohydrate in a cellular environment can be associated with lipid or protein of plasma membrane of cells.…”
Section: Fresh Semen Qualitymentioning
confidence: 99%
“…The stimulatory cycle comprised of 10 stimuli in each voltage, starting from 5-V, followed by voltage increases in steps of 1-V up to 12-V. Each electrical stimulus lasted for 3s with intermittent breaks of 2s. The stimuli were maintained for a duration of 10 min from the beginning of the procedure (Castelo et al 2010). The electroejaculator probe measured 15cm (length) and 1.3cm (diameter); and 12cm were inserted into the rectum of the male.…”
Section: Methodsmentioning
confidence: 99%
“…Several staining methods such as the brome-phenol blue (Toniolli et al 2010), the eosin-nigrosin (Moraes et al 2010), the diff-quick test (Kim et al 2011), the Cerovský (Fridrichová et al 2011), and the Williams-modified (Am-in et al 2011) are reported for sperm morphology analysis in the swine, that is the domestic species more closely related to the collared peccaries (Cavalcante-Filho et al 1998). In these last ones, only the eosin-nigrosin (Kahwage et al 2010) and the Bengal rose (Castelo et al 2010) staining are described for sperm evaluation, but comparisons among techniques are necessary in order to identify the most suitable for the species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Castelo et al. (,b) reported the first success in cryopreserving the collared peccary semen using Tris‐based extenders added of egg yolk (20%) and glycerol (3%). This protocol provided 37% motile sperm after thawing.…”
Section: Introductionmentioning
confidence: 99%
“…Since that only 3% glycerol was previously tested for collared peccaries semen (Castelo et al. ,b), the search for other concentrations that provide a better cryoprotection is justified to improve the protocol. Based on the fact that glycerol concentrations as higher as 6% are currently used for the semen freezing in domestic animals (Silva et al.…”
Section: Introductionmentioning
confidence: 99%